Enhancing convective heat transfer coefficient in a circular heat exchanger tube mounted with modified V-orifice (MVO): CFD analysis and correlations - Boonloi, Amnart; Jedsadaratanachai, Withada (Frontiers in Mechanical Engineering, 2026)
This study investigates the airflow dynamics and heat transfer (HT) profiles in a circular heat exchanger tube (CHET) mounted with a modified V-orifice (MVO) acting as a turbulator/vortex generator, which is a passive technique to enhance HT. A numerical modeling approach based on the finite volume method using a commercial software package was employed to provide detailed insights into the air flow profile, which is essential for the design of both the turbulator and the CHET system. The MVO is a turbulator derived from the orifice concept, an established engineering device, and has been adapted in combination with a V-shaped structure to effectively generate vortices and enhance HT. Key parameters expected to influence the flow and HT behavior were investigated. These include the ratio of the MVO thickness, b, to the CHET diameter, D (referred to as the blockage ratio, B-R), which was studied in the range of 0.05–0.30, and the ratio of the MVO spacing, P, to the CHET diameter (pitch ratio, P-R), which was considered at values of 1, 1.5, and 2. Attack angles of 30°, 45°, and 60° were examined for both + x and–x flow directions. The study covered turbulent flow conditions corresponding to Reynolds numbers in the range of 3,000–16000, representative of the operating conditions at the CHET inlet. The results indicate that MVO installation in the CHET acts as a flow obstruction, generating a pressure difference that induces vortex formation. These vortices play a key role in modifying the HT behavior, resulting in increased convective HT coefficients. The outcomes are summarized in forms of dimensionless variables. The highest observed HT enhancement reached 9.93 times that of the plain CHET, while the maximum thermal enhancement factor (TEF) was 1.92, obtained at an attack angle of 30°, P-R = 1, B-R = 0.25, in the +x fluid-flow direction at Re = 3,000.